PENGARUH KEMUDAHAN PENGGUNAAN DAN KEPERCAYAAN TERHADAP MINAT BELI ULANG MELALUI KEPUTUSAN PEMBELIAN DI TOKOPEDIA PADA GENERASI Z DI KOTA PEKANBARU - , Rendra Wasnury, Jose Armando Manurung , Deny Danar Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine the Effect of Ease of Use and Trust on Repurchase Intentions Through Purchase Decisions at Tokopedia in Generation Z in Pekanbaru City. The population in this study is the z generation of Tokopedia marketplace users in the last six months in Pekanbaru City. This study consists of four variables, including Ease of Use (X1), Trust (X2), Purchase Decision (Y) and Repurchase Intention (Z). The sample in this study amounted to 100 samples using the Purposive Sampling method. The method of analysis in this study uses path analysis (Path Analysis) with data processing using SPSS (Statistical Package of Social Science). Based on the hypothesis testing conducted, the results showed that (1) Ease of use has a positive and significant effect on purchasing decisions; (2) Trust has a positive and significant effect on purchasing decisions; (3) Ease of Use has a positive and significant effect on Repurchase Intention; (4) Trust has a positive and significant effect on Repurchase Intention; (5) Purchase Decision has a positive and significant effect on Purchase Intention; (6) Ease of Use has a positive and significant effect on Repurchase Interest through Purchasing Decisions; (7) Trust has a positive and significant effect on Repurchase Interest through Purchasing Decisions Keywords: Ease of Use, Trust, Purchase Decision, Repurchase Intention